The development of a new multimodal genre for corporate communication: the case of video CEO statements - Miguel Ruiz-Garrido; Juan Carlos Palmer-Silveira (EuroAmerican Journal of Applied Linguistics and Languages)
The digitization of the world is continuously developing, with corporate genres migrating to the web. Annual Corporate Reports (ACR) now appear in digital formats ranging from static PDFs to interactive websites. This shift significantly impacts report narratives, which are often enhanced by corporate videos, as they represent a versatile communication tool. This is particularly relevant for students, who are naturally digitally literate and accustomed to visual and auditory content. Our study has two objectives. From a research perspective, we aim to identify key multimodal features of Video CEO Statements (VCS). From a pedagogical standpoint, we will demonstrate how these videos enhance students' multimodal literacy within corporate digital genres. This, in turn, could improve essential business communication skills, including leadership, audience engagement, and digital communication strategies, thus equipping students with competencies that are vital for today’s corporate landscape.